Relationship between organizational citizenship behaviour and sales achievement at TM Southern region - Aziz, Fuziana (2011)
The study of Organizational Citizenship Behaviour (OCB) in an organization is related to the employees' good behavior towards organization where they work. It is important to understand the behavior of employee in organization especially the willingness and voluntarily behavior that helps towards company's performance and achievement. For these reasons employees' good behavior or OCB is the primary focus of this study. The data for this research was collected from 105 sales employees at TM Southern Region. The main objective of this research is to identify and examine the relationship between OCB of sales employees at TM Southern Region and their sales achievement. The correlation and regression analysis were conducted to evaluate respondent judgments. It is hope that we could reveal the OCB of sales employees is related to their sales achievement. From the survey done, the Courtesy of sales employees at TM Southern Region is the most significant towards their sales achievement. TM Southern Region should consider the OCB of their new sales employees when hiring them, to ensure a high sales achievement which will help in producing high profitability for the company.